Transparência e acumulação de cargos públicos: um estudo dos municípios da Paraíba no ano de 2023 - Leite, Felipe Porto Gomes (2024)
This study investigated the relationship between transparency in municipal public management and the practice of accumulating positions by public servants in the municipalities of Paraíba in the year 2023. Using statistical methods such as correlation analysis and multiple linear regression, the results revealed a low magnitude correlation between transparency and accumulation of positions. Furthermore, the analysis indicated that transparency did not have a statistically relevant impact on the accumulation of positions, while the size of the population was substantially associated with this practice. The findings suggest that factors other than transparency can more significantly influence the dynamics of local public management. This study, through empirical findings, contributes to a better understanding of the relationship between transparency and job accumulation in municipalities in Paraíba, offering relevant information for future research in the area.